Surgical depigmentation of gingiva using scalpel - Maria Subash Aaron Muthuraj; Arun Maradi; Fazal Ilahi Jamesha; Nimisha Gopal (Eastern Journal of Medical Sciences, 2020)
Smile and esthetics play a major role in improving a person’s physical appearance and also moral courage. Good alignment of teeth and proper exposure of gingiva are the fundamental factors influencing the smile and esthetics of a person. Overexposure of gingiva and excessive pigmentation of gingiva affect the smile and esthetics of a person deliberately. Excessive pigmentation of gingiva can be due to various reasons such as smoking, hormonal, racial, and underlying systemic disorders. Depigmentation techniques are commonly used in the management of patients with excessive melanin pigmentation due to racial reasons. Hereby, we report a case of surgical depigmentation of the upper anterior gingiva using a scalpel in a normal healthy patient with excessive melanin pigmentation.